The novel (Europe Hotel) by Farhad Pirbal in the perspective of cultural criticism - Sirwan Wahid Khzhr; Farhang Muzaffar Muhammad (Zanco Journal of Humanity Sciences)
This research under the title of (Farhad Pirbal's Novel (Hotel Europe) from the perspective of cultural criticism), an attempt to show and reveal the hidden texts in the novel, cultural criticism is one of the new theoretical trends in the world of literary criticism Yes, our research consists of introductions and two sections, the first part is specific to the theoretical side. In this section, we have tried to focus carefully on the concept, definition and history of the cultural criticism, and the definition of cultural impurity and insufficiency, and the second part is specific to side, namely by presenting and analyzing the novel (Hotel Europe) and revealing the origins of the novel in terms of cultural criticism. The results were then presented in a number of points, including classifying and sorting the sources, and finally translating the summary of the study into Arabic and English.